Silicon pillar thickness effect on vertical double gate MOSFET (VDGM) with oblique rotating implantation (ORI) method - Munawar Agus Riyadi, 1977-, author; Ismail Saad, author; Razali Ismail, author; IEEE International Conference on Semiconductor Electronics (2008 : Johor) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL